The Decline of Liberalism in Europe and how to Revive it - Jordi Franch Parella (Comparative Economic Research. Central and Eastern Europe, 2019)
The liberal world order has produced immense benefits for Europe and people across the planet. Beginning in the 18th and 19th centuries, liberalism reinforces the natural rights of man to life, liberty and property, and has transformed the world in ways that have improved the material and social circumstances of humankind. But the liberal order that has been in place in Europe since 1945, after two world wars, is showing signs of deterioration. Today, this liberal order is being challenged by a variety of forces. The essence of the European experience is the development of a civilization that considered itself to be a unity and yet was politically decentralized. Former free towns in Italy and the Low Countries became bastions of a self-governing middle class in the Middle Ages. However, with time, states tend to overgrow taking more and more resources, which results in the increase in taxes and public spending, excessive regulation, deficits and public debt. There is a fight between the advocates of two different ideals of the European Union, the non-liberal and the liberal vision. There is a consensus in that the market economy is the system that best produces the most, removing millions of people from poverty. But it is the unequal distribution of the wealth created that is often criticized. We examine the distribution of income, before and after taxes and transfers, concluding that market liberalization does not necessarily lead to increased social inequality. On the other hand, two of the most important threats challenging the liberal order in Europe are populist parties and protectionism. Finally, this paper suggests a way towards a future Europe, deepening the single market and economic integration, but transforming the obsolete and dysfunctional nation-states into other forms of decentralized political units.
Keywords: O52; P17; P59; 330; liberalism; Europe; single market; nation-state; decentralization